Social media use, knowledge, attitudes, and risky sexual behavior of HIV transmission: A survey among boarding school adolescent students in Indonesia - Ramadani, Regina Cahya; Ibrahim, Kusman; Mirwanti, Ristina; Maulana, Sidik; Jabareen, Raifa (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: Social media has many positive and negative influences on individuals, especially for adolescents related to HIV. However, little is known about how social media impacts HIV-related outcomes among adolescents in boarding schools. Objective: This study aims to investigate the social media use, knowledge, attitudes, and sexual behavior at risk of HIV transmission and their relationship with the demographic characteristics of adolescent students at boarding schools. Methods: This study was school-based and used a cross-sectional design. The questionnaires were used to assess social network site usage, knowledge, attitudes, and risky behavior. Cluster random sampling involved students (n = 214) from three boarding schools in Cirebon City, West Java, Indonesia, in 2022. Chi-square tests and Cramer’s V were used to explore correlations between social and demographic factors. Results: A considerable number of adolescent students exhibited high social media addiction (58.4%), with the majority possessing limited knowledge of HIV transmission (54.7%). Additionally, nearly half displayed a negative attitude towards preventing HIV transmission (47.2%), while only a small fraction engaged in risky behavior (2.8%). Bivariate analysis revealed that social media use was moderately associated with the type of social media application (φc = 0.246, p <0.05). Knowledge of HIV transmission exhibited a moderate correlation with age (φc = 0.331, p <0.05), education level (φc = 0.240, p <0.001), and exposure to information (φc = 0.269, p <0.001). Similarly, attitudes toward HIV prevention demonstrated moderate associations with age (φc = 0.341, p = 0.001), education level (φc = 0.317, p <0.001), and exposure to information (φc = 0.266, p <0.001). Furthermore, risky sexual behavior exhibited a strong association with exposure to pornographic content (φc = 0.730, p <0.001). Conclusion: The study found a high prevalence of social media usage among adolescents, coupled with low knowledge about HIV, negative attitudes, and risky behavior. Significant relationships were observed between social media use, knowledge, attitudes, and risky sexual behavior related to HIV transmission and demographic characteristics. This study emphasizes the vital role of nurses and healthcare professionals in implementing targeted educational interventions in boarding schools to address gaps in HIV risk knowledge influenced by social media, ultimately improving strategies for adolescents’ sexual health.